SISTEM INFORMASI DATA PULANG JAMAAH IKSASS SULAWESI BERBASIS WEB - Abdus Somad; Milka Afifah; Hijrah Hijrah; Syirva Nada; Diana Uzlifatil (Jurnal Riset Teknik Komputer, 2026)
The development of information technology has encouraged digital transformation in data management, including within religious organizations and congregational communities. At Pondok Pesantren Salafiyah Syafi'iyah Sukorejo, particularly in the IKSASS Sulawesi Putri Rayon, the management of congregants' departure data is still conducted manually, resulting in various issues such as delays in information delivery, recording errors, and difficulties in data tracking. The utilization of web-based information systems has been proven to improve efficiency and accuracy in data management [1]. Therefore, this study aims to design and develop a web-based information system for managing congregants' departure data to enhance the effectiveness and efficiency of data administration. The research methods employed in this study include literature review, observation, interviews, and system development using the Waterfall method, which consists of the stages of requirements analysis, system design, implementation, and testing. Structured system development methods such as Waterfall and other approaches have been widely applied in the development of web-based information systems [2], [3]. The system was developed using the PHP programming language and MySQL database and was designed with key features including congregant data entry, departure record management, data searching, and web-based reporting that can be accessed in real time. The results of the study indicate that the web-based information system facilitates the management of congregant data, improves recording accuracy, and accelerates the process of information presentation. The implementation of information systems in religious and congregational service sectors has also demonstrated improvements in service quality and transparency of data management [4], [5]. With the implementation of this system, it is expected that the administrators of the IKSASS Sulawesi Putri Rayon at Pondok Pesantren Salafiyah Syafi'iyah Sukorejo will be able to manage data in a more structured, transparent, and efficient manner.